Video Endoscopy-Guided Intrabronchial Spray Inoculation of Mycobacterium bovis in Goats and Comparative Assessment of Lung Lesions With Various Imaging Methods - Wedlich, Nadine; Figl, Julia; Liebler-Tenorio, Elisabeth M.; Köhler, Heike; von Pückler, Kerstin; Rissmann, Melanie; Petow, Stefanie; Barth, Stefanie A.; Reinhold, Petra; Ulrich, Reiner; Grode, Leander; Kaufmann, Stefan H. E.; et al. (Frontiers in Veterinary Science, 2022)
Bovine Tuberculosis (bTB) not only poses a zoonotic threat to humans but also has significant economic impact on livestock production in many areas of the world. Effective vaccines for humans, livestock and wildlife are highly desirable to control tuberculosis. Suitable large animal models are indispensable for meaningful assessment of vaccine candidates. Here we describe the refinement of an animal model for bTB in goats. The intrabronchial inoculation procedure via video-guided endoscopy in anesthetized animals, the collection of lungs after intratracheal fixation in situ and imaging of lungs by radiography were established in 3 goats using barium sulfate as surrogate inoculum. For subsequent infection experiments, four goats were infected with 4.7 x 102 colony forming units of M. bovis by intrabronchial inoculation using video-guided endoscopy with spray catheters. Defined amounts of inoculum were deposited at five sites per lung. Four age-matched goats were mock-inoculated. None of the goats developed clinical symptoms until euthanized at 5 months post infection, but simultaneous skin testing confirmed bTB infection in all goats inoculated with M. bovis. In tissues collected at necropsy, M. bovis was consistently re-isolated from granulomas in lymph nodes draining the lungs of all goats infected with M. bovis. Further dissemination was observed in one goat only. Pulmonary lesions were quantified by computed tomography (CT) and digital 2D radiography (DR). CT revealed mineralized lesions in all infected goats ranging from <5 mm to >10 mm in diameter. Small lesions <5 mm predominated. DR failed to detect small lesions and to determine the exact location of lesions due to overlapping of pulmonary lobes. Relative volume of pulmonary lesions was low in three, but high in one goat that also had extensive cavitation. CT lesions could be correlated to gross pathologic findings and histologic granuloma types in representative pulmonary lobes. In conclusion, video-guided intrabronchial inoculation with spray catheters, mimicking the natural way of infection, resulted in pulmonary infection of goats with M. bovis. CT, but not DR, presented as highly sensitive method to quantify the extent of pulmonary lesions. This goat model of TB may serve as model for testing TB vaccine efficacy.